2021
DOI: 10.3390/pediatric13030048
|View full text |Cite
|
Sign up to set email alerts
|

IgA Vasculitis Complicated by Both CMV Reactivation and Tuberculosis

Abstract: Immunoglobulin A (IgA) vasculitis is the most common systemic vasculitis in the pediatric population. We present the case of a patient with IgA vasculitis with nephritis who developed cytomegalovirus (CMV) infection followed by Mycobacterium tuberculosis infection. In the literature, there are a few cases of IgA nephropathy accompanied by reactivation of CMV or tuberculosis. To the best of our knowledge, this is the first reported case of IgA vasculitis complicated by both CMV reactivation and tuberculosis. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Latent viral infection reactivation has been considered in the setting of immunosuppression. CMV complicating HSP was observed in both children and adults after high-dose steroid therapy [ 53 , 54 ].…”
Section: Environment Microbial and Virus Infectionsmentioning
confidence: 99%
“…Latent viral infection reactivation has been considered in the setting of immunosuppression. CMV complicating HSP was observed in both children and adults after high-dose steroid therapy [ 53 , 54 ].…”
Section: Environment Microbial and Virus Infectionsmentioning
confidence: 99%
“…Hu et al [ 46 ] also reported that EBV can trigger HSP via cellular and humoral immunity. Several cases of HSP with CMV have suggested that CMV may be a contributing factor [ 47 , 48 , 49 ]. Shin et al [ 50 ] have reported that hepatitis B surface antigens play a role in HSP development.…”
Section: Discussionmentioning
confidence: 99%
“…As native IgAN is considered to be closely related to the pathogenesis of mucosal immunity, such as upper respiratory tract infection and intestinal infection [20], preceding infections might contribute to the onset or exacerbation of posttransplantation recurrent IgAN. Thus, there are several studies that reported IgAN or IgA vasculitis accompanied by CMV infection [21–23], yet the relationships between C1q deposition and infections have not been addressed in those studies. In our study, patients with peripheral C1q deposition in the Recurrent group had a higher incidence of endocapillary hypercellularity.…”
Section: Discussionmentioning
confidence: 99%